Comparison between fattening ability of Adal and Blackhead Somali sheep - Akalu, B.; Galal, E.S.E. (1981)
Thirty two ram lambs were included from the on-going selection breeding programme. These lambs consisted of the Adal and Black Head Somali (16 each) and were used to study the fattening ability of the two breeds and to compare the concentrate ratio. The average initial weights and age were 14.2 Kg and 123 days (SD = 11) respectively. The trial lasted for 97 days. Ration had highly significant affect on ADG and dressing percentage and significant effect on tail weight. Breed had no significant effect on the weights, ADG and all carcass traits. Breed ration interaction had no significant affect on all traits except on Kidney fat. Kilogramme feed consumed per kg liveweight gain for Adal and Black Head Somali fed on ration A was 6.26 and 6.16, and 8.28 and 8.65 for the two breeds on ration B respectively.